ReSA: architecture for resources sharing between clouds - Waqas, Ahmad; Muhammed Yusof, Zulkefli; Shah, Asadullah; Asif Khan, Mohammad (National University of Sciences and Technology, 2014)
Cloud computing has emerged as paradigm for hosting and delivering services over the Internet. It is evolved as a key computing platform for delivering on-demand resources that include infrastructures, software, applications, and business processes. Mostly, clouds are deployed in a way that they are often isolated from each other. These implementations cause lacking of resources collaboration between different clouds. For example, cloud consumer requests some resource and that is not available at that point in time. Client satisfaction is important for business as denying the client may be expensive in many ways. To fulfill the client request, the cloud may ask the requested resource from some other cloud. In this research paper we aim to propose a trust worthy architecture named ReSA (Resource Sharing Architecture) for sharing on-demand resources between different clouds that may be managed under same or different rules, policies and management.